Peningkatan Profesionalisme Guru Melalui Inovasi Strategi Pembelajaran - Wiwin Rif’atul Fauziyati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
This study aims to describe teacher professionalism through innovative learning strategies. The research method used in this study is descriptive qualitative method. This method is used to describe teacher professionalism through innovative learning strategies. The primary sources used in this article come from literature, scientific journals, and online news related to research problems. The data collection method is carried out by reading, studying, and recording various literature materials, scientific journals, and online news in accordance with the subject matter, then filtered and poured into a theoretical frame of mind so that a conclusion can be drawn. The results illustrate that innovative learning strategies that can be chosen and used by teachers in the classroom include: cooperative learning strategies (STAD models, and Jigsaw), computer-based learning strategies, and electronic-based learning strategies (E-Learning). Each of these learning strategies has different characteristics, which in their use can certainly adjust to the conditions of teachers and students. The introduction of new learning strategies can help teachers present material more engagingly and effectively, increase student engagement, and create a dynamic learning environment.